Circulating sTREM-1 as a Biomarker of Myeloid-Driven Inflammation in Breast Cancer: Diagnostic and Prognostic Significance: sTREM-1 and Myeloid Inflammation in Breast Cancer - Zhang, Jiazhennan; Yasheng, A-da-lai-ti·; Wang, Hu; Jia, Yizhen; Ai, Xiaoye; Jinsihan, Dilixiati· (Journal of Medical Biochemistry, 2026)
Background: Reliable circulating biomarkers reflecting tumor-related immune-inflammatory activation are of increasing interest in clinical biochemistry. Triggering receptor expressed on myeloid cells-1 (TREM-1) is a key amplifier of myeloid-driven inflammatory signaling, and its soluble form (sTREM-1) can be detected in peripheral blood. However, the clinical and biochemical relevance of circulating sTREM-1 in breast cancer remains insufficiently characterized.Methods: This single-center observational study included 132 patients with treatment-naive stage I–III breast cancer, 68 patients with benign breast disease, and 60 healthy controls. Serum sTREM-1 levels were measured in fasting blood samples, together with conventional biochemical and hematological parameters, including C-reactive protein (CRP), carbohydrate antigen 15-3 (CA15-3), carcinoembryonic antigen (CEA), and derived inflammatory indices (NLR, PLR, LMR, and SII). Associations between sTREM-1 and clinicopathological features, systemic inflammatory markers, and disease-free survival (DFS) were analyzed. Diagnostic performance was evaluated using receiver operating characteristic (ROC) analysis, and prognostic value was assessed using Kaplan–Meier curves and Cox regression models.Results: Serum sTREM-1 levels were significantly elevated in patients with breast cancer compared with both benign disease and healthy controls (P
Keywords: Breast cancer; sTREM-1; diagnosis; prognosis; immune inflammation; biomarker